UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK PADA MATA PELAJARAN KEWIRAUSAHAAN KELAS IX TKJ DI SMK NEGERI 1 LAHUSA - Roslinda Yupita Maduwu (Universitas Nias Raya, 2026)
The problem with this research is that students are less interested in the methods used by teachers in teaching, teachers dominate learning too much, and student learning outcomes do not meet the expected KKM criteria. The aim of this research is 1) to find out how the learning process in the Entrepreneurship subject in class This type of researchis Classroom Action Research (PTK). The research instruments are observation sheets, documentation, learning outcomes tests. The research subjects were 13 students in class XI TKJ SMK Negeri 1 Lahusa. The research resuits in cycle I averaged learning outcomes of 71,76 with a percentage of 76.92% and cycle II increased with average learning outcomes of 87,69 with a percentage of 92,30%. Conclusions, namely: 1) The Talking Stick Type Cooperative Leraning Type can improve student learning outcomes, because by implementing the Talking Type Cooperative Learning Model students are more active in learning activities, have courage and confidence in expressing opinions, are able to understand the material questions with the material that material that has been studied. 2) Student leraning outcomes in entrepreneurship subjects increased from an average of 71,76 to 87,69. Suggestions for school, especially teachers, to apply the Talking Stick Type Cooperative learning type to other subjects in accordance with this learning. Researchers who will use the Talking Stick Type Cooperative learning should be able to collaborate well with observers so as to improve the learning process to get optimal results. Teachers should always encourage students to be more active in learning.